Two new species of Entomelas (Nematoda: Rhabdiasidae), parasites of Barisia spp. and Mesaspis spp. (Reptilia: Sauria) in Mexico - Martínez-Salazar, Elizabeth A.; León-Règagnon, Virginia (Zootaxa, 2005)
Entomelas campbelli n. sp. (Rhabdiasidae) from the lungs of Barisia imbricata and Mesaspis gadovii (Sauria) and Entomelas floresvillelai n. sp. from B. imbricata, B. herrerae and M. viridiflava (Sauria) are described and illustrated. Both species are similar to E. duellmani in the equatorial location of vulva; E. campbelli resembles E. duellmani in measurements of the buccal capsule, but differs in the shape of the tail, body length, egg size, esophagus length and tail length/body length ratio; E. floresvillelai resembles E. duellmani by possessing a blunt tail, but differs in the body length, egg size, depth of the buccal capsule, length of the esophagus and tail length/ body length ratio. Entomelas campbelli differs from E. florevillelai in the shape of the anterior end and the tail, width of the body and buccal capsule, width of the esophageal bulb, egg size and esophagus length/body length ratio. These are the second and third species assigned to New World Entomelas and the second record of the genus from Mexico.